Functional outcome of conservative versus plate osteosynthesis in displaced midshaft clavicle fracture in manual labours - Mishra, Amit; Kumar, Dharmendra; Yadav, Ashok; Pandey, Deepak; Sinha, Abhinit Kumar (International Surgery Journal, 2017)
Background: Clavicle fracture is a one of most common shoulder injury which is commonly treated conservatively. Operative methods are used for open reduction and internal fixation of displaced fracture shaft clavicle with better functional outcome preserving the shoulder biomechanics needed for overhead manual workers. This study is aimed at study of functional outcome of different modalities of treatment used in treatment of displaced fracture midshaft clavicle in manual laborers. Methods: This study was conducted with permission of ethical committee in B.R.D Medical College, Gorakhpur, Uttar Pradesh, India. This study included 36 patients with closed displaced fracture midshaft fractures. Out of 36patients, 17 were treated conservatively using clavicle brace and sling and 19 patients were treated operatively by open reduction and internal fixation using reconstruction plate or AO pre-contoured plate. All patients were followed clinically and radiologically, regularly at 1 month duration for 18 months. Functional outcome both, conservative and operatively treated patients were assessed using constant and murley scoring system. Results: 17 patients treated conservatively had good to average functional results and 19 patients treated surgically had excellent functional outcome at 4 weeks of the treatment. At 12 weeks all fractures united well in operative group patients had better functional outcome with good range of shoulder abduction than conservative group of patients where in 4 patients fractures did not united and later underwent operative treatment to achieve fracture union. Average time of fracture healing in operative group was 8 weeks, less than time average time (12 weeks) taken by fracture healing in conservatively treated patients. Complication rate in conservatively treated group was tenting of skin and formation of discharging wound later, malunion, delayed fracture healing leading to shoulder stiffness and decreased shoulder abduction. Wound infection, implant failure or wound dehiscence like common complications were not seen in operative group. Conclusions: In manual laborers, clavicle fractures treated operatively had united early with excellent functional outcome and better shoulder abduction and early return to work with no complications in comparison to fractures treated conservatively.